The application of method AHP to choose a construction enterprise for partnering cooperation - Radziszewska-Zielina, Elżbieta (Budownictwo i Architektura / Civil and Architectural Engineering, 2014)
In construction industry partnering is a long-term commitment between two or more organizations aimed at achieving particular business objectives by maximizing the effectiveness of each participant’s resources. As opposed to competition, partnering is characterized by cooperation rather than rivalry which may transform into fighting. Partners cooperate, striving for the implementation of a construction project, which is their common objective, and for mutual benefits. The present author has developed a research model of the partnering relations of construction enterprises. This paper presents a non-standard application of AHP multi-criteria method in choosing a construction enterprise for partnering cooperation during the construction project implementation.